Análise fitoquímica de Ocotea odorifera (Lauraceae), Piper leavicarpu (Piperaceae) e avaliação da atividade biológica dos metabolitos isolados - Maciel, Dayany da Silva Alves [UNIFESP] (2014)
Ocotea odorifera (Lauraceae) is popularly known as “sassafras” or “sassafras-cinnamon” while Piper laevicarpu (Piperaceae) is known as “falsa-pimenteira”. These two species are from the Brazilian Atlantic Forest biome. Previous studies conducted in our laboratory showed that the methanol extract of aerial parts of O. odorifera and dichloromethane extract of the leaves of P. laevicarpu exhibit antitumor and antiparasitic activity, respectively. Thus, in this study, the phytochemical analysis of these extracts biological monitoring aimed to isolate and identify the compounds that are cytotoxic activity for B16F10 Nex2 (murine melanoma) in O. odorifera, and P. laevicarpu antileishmanial and antitrypanosomal activity. For this purpose, the crude extracts were individually subjected to different chromatographic procedures (SiO2 normal phase and Sephadex LH-20). In these processes, five compounds were identified with cytotoxic activity in O. odorifera 1 (eugenol), a mixture of 2 + 3 (4-allyl-2,6-dimethoxyphenol and dioctyl adipate), 4 (isoeugenil acetate) and 5 (sitosterol), 1 and 2 have not yet been previously described in the species under study. In P. laevicarpu was isolated new compound a cyclic amide laevicarpin (6) as natural product, which noted a great potential antiparasitic in vitro. For this substance, the potential for a trypomastigote forms of T. cruzi showed IC50 values determined as 14.75 µM/mL is indicative of excellent activity for T. cruzi with low toxicity compared to positive control benznidazole (42.5 M/mL). These result showed the presence of species in the molecules under study can be used as a prototype for the development of new drugs with anti-tumor and / or anti-parasitic action. .